2023
DOI: 10.1186/s12885-023-10612-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukaemia: population-based study of epidemiology and outcome with ATRA and oral-ATO from 1991 to 2021

Abstract: Background The epidemiology and treatment of acute promyelocytic leukaemia (APL) are changing. We have incorporated oral arsenic trioxide (oral-ATO) into induction/maintenance. Methods Newly-diagnosed APL from 1991 to 2021 divided into three 10-year periods were studied to define its epidemiology and how oral-ATO impacted on its outcome. Primary endpoints included APL incidence, early deaths (ED, first 30 days), and overall survival (OS). Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, recent data utilizing the US National Inpatient Sample database from 2016 to 2019 suggest an increasing incidence with age, with a peak incidence of 0.62 (per 100,000 inhabitants) in patients aged 75-79 years as compared to APL's annual age-adjusted incidence rate of 0.28 (per 100,000 inhabitants) [16]. These results were recently confirmed by a retrospective cohort analysis from the Acute Promyelocytic Leukaemia Asian Consortium Project, which included 761 newly diagnosed APL patients between 1991 and 2021 [17]. The authors observed an increasing incidence of APL in elderly (60-79 years) patients, rising from 0.22 in 1991-1999 to 0.53 in 2010-2021.…”
Section: Apl In the Elderly Adult 21 Epidemiology Of Elderly Patientsmentioning
confidence: 76%
“…However, recent data utilizing the US National Inpatient Sample database from 2016 to 2019 suggest an increasing incidence with age, with a peak incidence of 0.62 (per 100,000 inhabitants) in patients aged 75-79 years as compared to APL's annual age-adjusted incidence rate of 0.28 (per 100,000 inhabitants) [16]. These results were recently confirmed by a retrospective cohort analysis from the Acute Promyelocytic Leukaemia Asian Consortium Project, which included 761 newly diagnosed APL patients between 1991 and 2021 [17]. The authors observed an increasing incidence of APL in elderly (60-79 years) patients, rising from 0.22 in 1991-1999 to 0.53 in 2010-2021.…”
Section: Apl In the Elderly Adult 21 Epidemiology Of Elderly Patientsmentioning
confidence: 76%
“…In a recent study analyzing data from 2000 to 2021, there was lower mortality attributed to APL-DS and intracranial hemorrhage in academic centers. Conversely, mortality rates in non-academic centers persisted at elevated levels, highlighting the importance of centralizing care and the early recognition of subtle symptoms by trained personnel (25).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Moreover, novel data have shown that intracranial hemorrhage has been the most significant contributor of early treatment failure and has led to ED in 42%. 6 Although hemorrhagic complications have always received the most attention in APL, the rate of thrombotic complication, at the opposite end of the spectrum, has been overlooked. It is thought that the incidence of thrombosis in APL is higher than in all other types of AML, but there are still little data on this complication.…”
Section: Introductionmentioning
confidence: 99%